Appropriateness of hospitalization in a ward of internal medicine--using the Appropriateness Evaluation Protocol. - Vieira, Nuno B (2006)
The Appropriateness Evaluation Protocol (AEP) is an instrument to study the appropriate use of hospital beds based in objective criteria that classify a hospital admission as appropriate or inappropriate.Evaluate the appropriateness of hospital admissions and stays of the patients of our Internal Medicine Department using the concurrent version of AEP.Transversal study where was evaluated the clinical record of the patients admitted to our Department of Internal Medicine on March 13th of 2003, excluding all these who were admitted the day of the study. We analyzed demographic and clinic parameters and the appropriateness of hospital admission and stay using the AEP.22 patients fulfilled the inclusion criteria, 54.5% of male gender with a average age of 70.7 years. All the admissions were considered appropriate. The most common criteria was the need of intravenous therapy (100%), followed by the sudden lost of corporal mobility (12.3%). 27.3% of stays were considered inappropriate on the day of the study. The most common criteria of appropriateness was the need of intravenous therapy (93.7%). The most usual reason of inappropriate stay was the existence of planned discharge, but without the order written down in the clinical file (66.7%).The AEP allows an efficient evaluation of the appropriateness of the hospital admissions and stays in a Health Unit, being used for a better utilization of resources. In our department all admissions were justified and about a quarter of stays were considered inappropriate using the AEP.